Mesenchymal stromal cells: a novel therapy for the treatment of chronic obstructive pulmonary disease?. Issue 6 (13th April 2018) - Broekman, Winifred; Khedoe, Padmini P S J; Schepers, Koen; Roelofs, Helene; Stolk, Jan; Hiemstra, Pieter S
Abstract : COPD is characterised by tissue destruction and inflammation. Given the lack of curative treatments and the progressive nature of the disease, new treatments for COPD are highly relevant. In vitro cell culture and animal studies have demonstrated that mesenchymal stromal cells (MSCs) have the capacity to modify immune responses and to enhance tissue repair. These properties of MSCs provided a rationale to investigate their potential for treatment of a variety of diseases, including COPD. Preclinical models support the hypothesis that MSCs may have clinical efficacy in COPD. However, although clinical trials have demonstrated the safety of MSC treatment, thus far they have not provided evidence for MSC efficacy in the treatment of COPD. In this review, we discuss the rationale for MSC-based cell therapy in COPD, the main findings from in vitro and in vivo preclinical COPD model studies, clinical trials in patients with COPD and directions for further research.